Perancangan Tingkahlaku Organisasi: Kajian Dikementerian Hal Ehwal Ugama (KHEU), Negara Brunei Darussalam - Syed Ismail, Sharifah Hayaati (Jurnal Usuluddin, 2005)
This article explores on Muslims organization planning system towards an ethical organizational behavior. It focuses on three major questions; first, what are the values adopted in the public management of the Ministry of Religious Affair of Brunei, second, how the values are implemented and, thirdly, the strength and weaknesses (if any) in the planning system towards inculcating values and ethics. Finding shows that the Ministry is adopting good values and ethics to the civil servant but lease on regular planning and enforcement. It is suggested in this paper that an ethical organizational behavior needs a strategic and regular planning through 5 approaches i.e. giving awareness, in-depth understanding, practicality, consistent evaluation and lead through example.